Pengaruh Kompetensi, Independensi dan Pengalaman Kerja Terhadap Kualitas Audit Dengan Etika Auditor Sebagai Variabel Pemoderasi (Studi Empiris pada Inspektorat Kabupaten/Kota Surakarta, Karanganyar dan Boyolali) - Mahardikka, Shinta; , Dr. Zulfikar, SE, M.Si (2017)
The objectives of this research to empirically analyze the influence of competency, independency and work experience on audit quality and to the influence of competency,ndependency and work experience to audit quality is moderated by auditor ethics, especially in the auditor and P2UPD working in Inspectorate district/city of Surakarta, Karanganyar and Boyolali.The population in this research are all auditors an P2UPD who worked on the inspectorate district/city of Surakarta, Karanganyar and Boyolali. Sample collection method by using the technique of sampling purposive. The samples used in the study totalled 45 respondents. Primary data collection method used is questionnaire method. The data are analyzed by using Moderate Regression Analyze (MRA).The result showed that the effect on the competency, independency and work experience positive effect on audit quality, but after being moderated by the ethics of auditors variable competency, independency and work experience negative effect on audit quality. The coefficient of determination shows that jointly competence, independence, work experience and ethics of auditors contriibuted to the dependent variable (quality audit) is 86,1% while the remaining 13,9% is influence by other factors outside of observation.